Quantitative lingual, pharyngeal and laryngeal ultrasonography in swallowing research: a technical review. - Chi-Fishman G (Clinical Linguistics & Phonetics)
Because of its distinct advantage in radiation-free soft tissue imaging, ultrasonography has been widely used to study lingual, pharyngeal, hyoid, laryngeal, and even esophageal action during swallowing in individuals of all ages. Qualitative ultrasonographic observations have made considerable contributions to our understanding of deglutition. Quantitative ultrasonographic swallowing research has also grown by leaps and bounds over the years with advances in imaging technologies and analytical methodologies. As a technical primer for new investigators, this paper reviews the modem methods for quantitative analysis in ultrasonographic swallowing research. The intended outcome is a basic understanding of the application of ultrasonography with various analysis options to the quantitative study of the deglutitive action of selected upper aerodigestive structures. Though proven useful for swallowing research, ultrasonography has inherent limitations and methodological issues. Future technological advancement and sophisticated image processing and analysis algorithms will resolve some of these issues.